The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4103/0970-4388.199233
|View full text |Cite
|
Sign up to set email alerts
|

Genetic specificity to 6-n-propylthiouracil and its association to dental caries: A Comparative study

Abstract: Dental caries is multi-factorial. No significant correlation between susceptibility of mother and child to genetic sensitivity exists, and genetic sensitivity is not the only criteria for severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Our patients ranged from 12 to 42 years-old, which was similar to the range to previous studies on the association of the PROP sensitivity test and dental caries. 32 , 33 , 34 , 35 Most patients were recruited into the study after wearing fixed appliances for 2 to 9 months. This duration is long enough to observe changes related to dental caries development.…”
Section: Discussionmentioning
confidence: 99%
“…Our patients ranged from 12 to 42 years-old, which was similar to the range to previous studies on the association of the PROP sensitivity test and dental caries. 32 , 33 , 34 , 35 Most patients were recruited into the study after wearing fixed appliances for 2 to 9 months. This duration is long enough to observe changes related to dental caries development.…”
Section: Discussionmentioning
confidence: 99%
“…51 As the non-taster phenotype and genotype are also associated with reduced sensitivity to sweet taste and liking sweets, 43,52 numerous phenotype taste tests have also been conducted, relating the non-taster status of PROP to dental decay and dental caries. [53][54][55][56][57][58][59][60][61][62][63][64][65][66] Generally, studies have found that PROP non-tasters were at higher risk of decayed, missing, and filled surfaces and caries experience compared to tasters. Medium tasters were also at higher risk compared to supertasters.…”
Section: Oral Healthmentioning
confidence: 99%